Academic Leadership in Organizational Cultural Transformation: Building a Biah Lugawiyyah Ecosystem in the Pesantren Environment - Akhmad Fauzi Hamzah (Lembaga Pengembangan Penelitian, Pengabdian, dan Publikasi, 2026)
The transformation of the language environment (bi'ah lughawiyyah) in Islamic boarding schools is frequently hampered by weak managerial intervention, relying exclusively on classroom teaching methods. This study aims to analyze the role of academic leadership in transforming organizational culture to build a sustainable bi'ah lughawiyyah ecosystem at Universitas Islam Internasional Darullughah Wadda'wah. This qualitative case study collected field data through observation, in-depth interviews with key informants, and documentation studies. The results reveal that leaders successfully engineered the culture of the language ecosystem through four main strategies: internalizing the integrated educational vision (Hadhari), formalizing instructional policies through a tiered disciplinary structure, integrating physical and symbolic environmental engineering (applying lauhatul ism and jasus instruments), and demonstrating prophetic leadership role modeling. In conclusion, the robustness of the bi'ah lughawiyyah ecosystem is the result of organizational culture engineering structurally and spiritually orchestrated by top leadership, rather than mere pedagogical flexibility. This research contributes by providing a managerial governance model framework for other Islamic higher education institutions to maintain language traditions in the modern era.